Peranan Syariat Islam, Negara Dan Masyarakat Dalam Memerangi Hoax - Ramdani, Ramram Mansur; Abidin , Yusuf Zainal; Aep Kusnawan; Muhamad Zuldin (Indo Publishing, 2025)
This study aims to highlight the role of Islamic Sharia, the state and society in maintaining national stability and preserving public interests by combating hoaxes. At the beginning of the discussion, the researcher explains the definition of a hoax, the purpose of its creation and the effects it has on society in general. The researcher then shows how Islamic Shari'ah takes preventive action against the emergence of hoaxes and how Islamic Shari'ah combats hoaxes that have already emerged. The researcher presents the role of the state and society from different perspectives in combating hoaxes. The methodology used in the research is a qualitative approach by conducting library research (literature review) on references related to the research title. The results show that combating hoaxes has a close relationship with maintaining the stability of the country and maintaining the public interest, so it should be a shared responsibility.